Effect of root canal preparation, type of endodontic post and mechanical cycling on root fracture strength - Rippe, Marilia Pivetta [UNESP]; Santini, Manuela Favarin; Souza Bier, Carlos Alexandre; Baldissara, Paolo; Valandro, Luiz Felipe (Universidade de São Paulo (USP), Faculdade de Odontologia de Bauru, 2014)
Objective: To evaluate the impact of the type of root canal preparation, intraradicular post and mechanical cycling on the fracture strength of roots. Material and Methods: Eighty human single rooted teeth were divided into 8 groups according to the instruments used for root canal preparation (manual or rotary instruments), the type of intraradicular post (fiber posts-FRC and cast post and core-CPC) and the use of mechanical cycling (MC) as follows: Manual and FRC; Manual, FRC and MC; Manual and CPC; Manual, CPC and MC; Rotary and FRC; Rotary, FRC and MC; Rotary and CPC; Rotary, CPC and MC. The filling was performed by lateral compactation. All root canals were prepared for a post with a 10 mm length, using the custom # 2 bur of the glass fiber post system. For mechanical cycling, the protocol was applied as follows: an angle of incidence of 45 degrees, 37 degrees C, 88 N, 4 Hz, 2 million pulses. All groups were submitted to fracture strength test in a 45 degrees device with 1 mm/min cross-head speed until failure occurred. Results: The 3-way ANOVA showed that the root canal preparation strategy (p<0.03) and post type (p<0.0001) affected the fracture strength results, while mechanical cycling (p=0.29) did not. Conclusion: The root canal preparation strategy only influenced the root fracture strength when restoring with a fiber post and mechanical cycling, so it does not seem to be an important factor in this scenario.
Keywords: Post and core; Root canal preparation; Aging